On the Proposed Interstellar Origin of the USG 20140108 Fireball - Peter G. Brown; Jiří Borovička (The Astrophysical Journal, 2023)
A critical review of the evidence for the interstellar origin of the USG 20140108 fireball is presented. Examining United States Government (USG) fireball velocities where independent data are available shows the former to have significant (10–15 km s ^−1 ) uncertainties at large speeds and highly variable radiant accuracy, with average errors in excess of 10°. The ablation model fits to the observed lightcurve are possible for normal chondritic impactors only assuming low speeds. To match the high speed and low fragmentation height of the USG 20140108 fireball would require a high-density/strength object with low drag and a highly aerodynamic shape not made of iron. We suggest the simplest explanation for the unusual characteristics of USG 20140108 is that the speed, in particular, is substantially overestimated.